Pengaruh perceived value, kualitas pelayanan dan kepuasan konsumen terhadap minat beli ulang pada Distro Agung Sungai Penuh - Efdison, Zefri; Yelnim, Yelnim; Yadewani, Dorris; Erni Febrina Harahap; Medi.yaya2017@gmail.com; Putra (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the effect of perceived value, service qualityand consumer satisfaction on repurchase interest at the Agung Sungai Penuh distribution.In this study due to the large and unknown population. The samples taken were consumerswho made purchases at the Great Distro of Sungai Penuh City during the research periodor the minimum limit of 80 was obtained from 20 x the number of variables in this study.The sampling method in this study is the accidental sampling method, namely the samplingis based on the fact that they happen to appear in the research object. The results showedthat Perceived Value had a significant effect on repurchase interest. service quality has asignificant effect on repurchase intention. consumer satisfaction has a significant effect onrepurchase intention. The magnitude of the influence of 81.8% between Perceived Value(X1), service quality (X2) and consumer satisfaction (X3) on repurchase interest at theGreat Distro of Sungai Penuh City, while 18.2% can be explained by other reasons outsidethe study. this.